1979
DOI: 10.1007/bf00431026
|View full text |Cite
|
Sign up to set email alerts
|

Effect of long-term training and acute physical exercise on red cell 2,3-diphosphoglycerate

Abstract: A statistically significant 10% increase (p less than 0.005) in mean red cell 2,3-diphosphoglycerate (2,3-DPG) concentration, concomitantly with a mean 16% increase (p less than 0.001) in the predicted maximal oxygen uptake (VO2max) was observed in 29 recruits, who were studied during 6 months of physical training in military service. The increase in 2,3-DPG was higher, the lower the initial 2,3-DPG and VO2max levels. The mean initial 2,3-DPG level was higher in the subjects with a higher initial VO2max. A str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

1980
1980
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…The degree of the increase in 2,3-DPG and P50 value seems to be dependent on training intensity. It tended to relate inversely to MCHC and I-lb concentration, which is in agreement with other investigations (4,15). As shown previously, endurance training leads to a reduction in the mean red cell density indicating the presence of a higher portion of young erythrocytes in blood (10).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The degree of the increase in 2,3-DPG and P50 value seems to be dependent on training intensity. It tended to relate inversely to MCHC and I-lb concentration, which is in agreement with other investigations (4,15). As shown previously, endurance training leads to a reduction in the mean red cell density indicating the presence of a higher portion of young erythrocytes in blood (10).…”
Section: Discussionsupporting
confidence: 92%
“…Physical training induces many adaptive mechanisms, i.e., changes in the cardiovascular system, the muscle fiber composition, and an increase in the maximal oxygen uptake. Moreover, long-lasting exercise facilitates oxygen uncoupling from hemoglobin due to a rightward shift of the oxygen dissociation curve caused by an increase in red cell 2,3. diphosphoglycerate (2,3-DPG) (15). Furthermore, alterations of blood composition, such as a decrease in the hemoglobin (Hb) concentration, hematocrit (Hct), and mean corpuscular hemoglobin concentration (MCHC), the so-called sports anemia, are described.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that athletes have a higher baseline 2,3-DPG level than untrained subjects (Taunton et al, 1974;Remes et al, 1979;Brodthagen et al, 1985;Ricci et al, 1988). There is a significant positive relationship between the resting concentration of 2,3-DPG and VO 2max (Remes et al, 1979;Mairbäurl et al, 1983;Czuba et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…After low-intensity endurance exercise, 2,3-DPG tends to increase (Remes et al, 1979;Meen et al, 1981). However, it should be noted that basal 2,3-DPG level and the 2,3-DPG response to exercise also depend on the sports level of the subjects (Kuński and Sztobryn, 1976;Remes et al, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…1. In other words,the increment of treadmill endurance time and maximum oxygen uptake may be due to the increased mitochondrial enzyme activity (HOLLOSZY et al,1971)and/or red cell 2,3 diphosphoglycerate concentration (REMES et al, 1979),even if blood flow in the lower extremity is not increased by the training.…”
mentioning
confidence: 99%